1977
DOI: 10.1530/acta.0.0860754
|View full text |Cite
|
Sign up to set email alerts
|

Hla-Bw35 and B5 in Japanese Patients With Graves' Disease

Abstract: Thirty-three Japanese patients with Graves' disease and 106 healthy controls living in the Kagoshima area, the southernmost part of the Japanese mainland, were HLA typed by the NIH method. None of them were related to each other. The only antigen showing an increased frequency in Japanese patients with Graves' disease was HLA-BW35 (corrected P < 0.02). A decreased frequency of B5 in the patients was also statistically significant (corrected P < 0.02).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…There is strong familial tendency as well as ethnic HLA association, namely A2B46DR9 in Chinese, B35 and B46 in Japanese and A1B8DR3 in Caucasians. 4,[8][9][10][11] We showed that post-SCT AITD in Chinese has the same HLA and donor sex associations as in de novo AITD. Three factors may have triggered such HLA-related AITD: namely, inherent patient susceptibility, the effect of conditioning chemotherapy and radiotherapy, and the graftversus-host effect of the infused lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong familial tendency as well as ethnic HLA association, namely A2B46DR9 in Chinese, B35 and B46 in Japanese and A1B8DR3 in Caucasians. 4,[8][9][10][11] We showed that post-SCT AITD in Chinese has the same HLA and donor sex associations as in de novo AITD. Three factors may have triggered such HLA-related AITD: namely, inherent patient susceptibility, the effect of conditioning chemotherapy and radiotherapy, and the graftversus-host effect of the infused lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al reported a case with a rare combination of autoimmune disorders, including Graves' disease, AIH and mixed connective tissue disease, that might be caused by each of the sensitive HLA antigens of these disorders [11]. Our patient had positive A2 and B35, which has been related to Graves' disease in Japanese [12,13], and also had DR4, which has been correlated with type 1 DM and AIH in Japanese [14][15][16]. Thus, in our case, the possibility exists that these three disorders might be induced by the combination of these HLA antigens.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, HLA-DW3/ DR3 is known to be in strong linkage disequilibrium with HLA-B8 (Thorsby & Piazza, 1976). In the Japanese where the HLA-B8 and -DW3/ DR3 are virtually absent, Graves' disease was found to be associated not with HLA-B8, but with BW35 Kawa et al, 1977;Nakao et al, 1978). Moreover, in the Japanese the association with HLA-BW35 seems to be secondary to an increase in an HLA-D determinant (HO) which is different from HLA-DW3 (Sasazuki et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the definite association between Graves' disease and HLA (Grumet et al, 1975;Farid et al, 1976;Kawa et al, 1977), no such relation has been shown for Hashimoto's thyroiditis (Bode et al, 1973;Farid et al, 1975Farid et al, , 1976van Rood et al, 1975;Mayr et al, 1976, Konishi et al, 1977. However, most studies of Japanese patients with these diseases only concern the antigens of the A, B and C segregant series.…”
mentioning
confidence: 98%